Characterization of LiNbO3 powder prepared by citrate gel method - Onnom S. (2014)
Lithium niobate powder (LiNbO3) were synthesized by citrate gel method using LiNO3, Nb2O5, citric acid and HF as starting materials. LiNO3 was dissolved in distilled water that activated into LiOH. Nb2O5 was dissolved in minimum amount of HF at 37°C for 20 h. that activated into NbF5. Then citric acid, LiOH, and NbF5 were mixed in stoichiometric ratio. On heating at 100°C for 3-4 h. a yellowish gel is formed. Lithium niobate powders were obtained after calcination at 550-700°C. The effect of calcination temperature at various temperatures ranging from 550°C to 700°C were investigated. The phase and chemical composition of the synthesized powders were characterized by using XRD, SEM, TEM, FTIR and EDX. We found that the lithium niobate crystallize phase formed when the calcination temperature at 650°C with average particle size of around 100 nm. © 2008 Trans Tech Publications, Switzerland.